Complete chloroplast genomes of 11 Sabia samples: Genomic features, comparative analysis, and phylogenetic relationship - Chen, Qiyu; Chen, Chunling; Wang, Bo; Wang, Zehuan; Xu, Wenfen; Huang, Yuan; Sun, Qingwen (Frontiers in Plant Science, 2022)
The genus Sabia is a woody climber belonging to the family Sabiaceae, order Proteales. Several species of this genus have been utilized as medicines for treating diseases, such as rheumatic arthritis, traumatism, hepatitis, etc. However, the lack of molecular data has prevented accurate identification and refinement of taxonomic relationships in this genus. In this study, chloroplast genomes of 11 samples of the genus Sabia were assembled and analyzed. These chloroplast genomes showed a typical quadripartite structure and ranged in length from 160,956 to 162,209 bp. The structure of the genomes was found to be relatively conserved, with 130 genes annotated, including 85 coding genes, 37 tRNA genes, and 8 rRNA genes. A total of 78–98 simple sequence repeats and 52–61 interspersed repeats were detected. Sequence alignment revealed 11 highly variable loci in chloroplast genomes. Among these loci, ndhF-ndhD achieved remarkably higher resolution than the other regions. In addition, phylogenetic analysis indicated that Sect. Pachydiscus and Sect. Sabia of Sabia did not form two separate monophyletic groups. The divergence time calculated based on the Reltime method indicated that the evolutionary branches of Sabia and Meliosma started to form approximately 85.95 million years ago (Mya), and the species within Sabia began to diverge approximately 7.65 Mya. In conclusion, our study provides a basis for comprehensively exploring the phylogenetic relationships of Sabia. It also provides a methodological basis and data support for establishing a standardized and scientific identification system for this genus.